패션 VMD 교과목 개발을 위한 직무중요도 요인 분석 - 엄윤선; Youn-sun Eum; 박옥련; Ok-lyun Park (한국디자인포럼, 2016)
연구배경 소비자는 21세기 감성의 시대에서 체험과 상징을 중시하고, 글로벌한 감각적 소비 및 가치 지향적인 구매를 하고 있어 그 어느때보다도 패션 산업체의 요구에 맞는 인재 양성의 필요성이 대두되고 있다. 따라서, 유기적이면서도 능동적인 비쥬얼 머천다이저의 역량을 함양시킬 수 있는 교과목 개발이 필요하다. 연구방법 이에 본 연구는 패션기업 실무자와 패션관련학과 재학생을 대상으로 각각 200부의 설문을 배부하여 158부와 180부를 최종 자료 분석에 사용하였다. 연구결과 요인분석결과 매장유지관리/패션정보분석/브랜드전략수립/매장연출구성의 4개요인으로 분류 · 명명하였다. 집단 간 직무중요도 차이 조사 결과 패션실무자 집단은 현장 실행 중심의 VMD 직무인 매장유지관리. 매장연출구성 요인을 중요하게 생각하고 있는 것으로 나타나 실무교육 확대가 중요함을 알 수 있다. 결론 집단 간 요인별 세부항목별 차이를 분석한 결과, 현장 전개중심의 교과목 도입이 필요하며 패션산업체의 직무요구와 재학생 간의 직무인지도에 큰 차이가 있어 이론중심의 교육이 아닌 실무적용 교육모델이 필요함이 나타났다. 매장연출구성요인은 패션실무자와 재학생 집단 간에 가장 큰 차이가 나타난 요인으로 패션 업계에서 요구하는 현장 실행형 비주얼 머천다이저의 역량 강화를 위한 현장실습 교과목의 도입이 필요한 것으로 조사되었다. Background Consumers lay stress on the experience and symbol and doing global sensuous consumption and value-oriented purchase in the age of sensitivity of the 21st century. Thus, the necessity of cultivation of talented individuals suited to the demand of fashion industry has come to the fore than ever before. Accordingly, development of subjects capable of cultivating capability of organic and active visual merchandisers is necessary. Methods Thus, this study distributed 200 questionnaires to the hands-on workers in fashion companies and students attending fashion-related departments. 158 sheets and 180 sheets were used for analysis of final data. Result After carrying out factor analysis, this study classified and named the results as 4 factors of maintenance of shop, analysis of fashion information, establishment of brand strategy and composition of shop presentation. This study investigated the differences in job importance between groups. Hands-on workers group puts emphasis on the factors of maintenance of shop and composition of shop presentation that are the onsite performance-centered job duties of VMD. The result implicates importance of expanding practical education. Conclusion Analysis on the differences between detailed items by the factors between groups shows that introduction of onsite development-centered subjects is necessary showing a big difference between job demands of fashion companies and job awareness of students, which shows the necessity of a practical education model, not theory-centered education. Composition of shop presentation factor showd the biggest difference between hands-on workers and students, indicating that introduction of a field training subject for strengthening capability of practical visual merchandisers fashion industry demands is necessary.